Differences of EST-SSR and genomic-SSR markers in assessing genetic diversity in poplar - Song, Yue-peng; Jiang, Xi-bing; Zhang, Man; Wang, Ze-liang; Bo, Wen-hao; An, Xin-min; Zhang, De-qiang; Zhang, Zhi-yi (Forestry Studies in China, 2012)
We analyzed the genetic differences of 16 poplar clones between genomic-SSR and EST-SSR markers. The statistical results show that the average number of alleles detected by genomic-SSR was 4.1, Shannon＇s index 1.0646, observed heterozygos- ity 0.4427 and expected heterozygosity 0.5523, while for the EST-SSR, the average number of alleles was 2.8, Shannon＇s index 0.6985, observed heterozygosity 0.2330 and expected heterozygosity 0.4684. Cluster analysis indicated that the EST-SSR capacity of genotypic identification was more precise than that of genomic-SSR. These resuks reveal that EST-SSR and genomic-SSR have statistically significant genetic differences in polymorphism detection and genotypic identification. These differences could provide a theoretical basis for the rational use of SSR markers in species diversity and other related research.